2011
DOI: 10.1177/1066896911408304
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Gastrointestinal Stromal Tumor (GIST) on Transurethral Resection of the Prostate

Abstract: Gastrointesinal stromal tumors (GISTs) are the most common mesenchymal neoplasms of the gastrointestinal tract and they show differentiation towards interstitial cells of Cajal (ICC). Herein, we describe a case of a 60-year-old man presenting with symptoms mimicking adenomatous hyperplasia of the prostate that was subjected to repeated transurethral prostatectomies. Histologic and immunohistochemical examination showed a neoplastic process with characteristics consistent with GIST. Imaging studies confirmed a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…[9] The malignancy standard was debatable, and the criteria accepted by most researchers are deep intramuscular, infiltration of muscularispropria, diameter of neoplasms >5 cm, presence of mitotic figures (one or more per 50 high-power field), and coagulative necrosis and pleomorphism. [1] National Comprehensive Cancer Network (NCCN) published that the multiple disciplinary team (MDT) was important for the treatment of GIST. [10] The combination of iconography evidence and the pathologic analysis lead to the final diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[9] The malignancy standard was debatable, and the criteria accepted by most researchers are deep intramuscular, infiltration of muscularispropria, diameter of neoplasms >5 cm, presence of mitotic figures (one or more per 50 high-power field), and coagulative necrosis and pleomorphism. [1] National Comprehensive Cancer Network (NCCN) published that the multiple disciplinary team (MDT) was important for the treatment of GIST. [10] The combination of iconography evidence and the pathologic analysis lead to the final diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…For the big tumor more than 10 cm, adjuvant therapy was necessary for the preoperative treatment of the tumor. Though some of the early publication reported the diagnosis by CD117 positivity will lead to prompt imatinib mesylate introduction and avoidance of the surgical treatment, [1] it is hard for the only imatinib treatment for the huge GIST.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The origin of EGISTs remains to be elucidated; however, GISTs and EGISTs have been confirmed to share various clinicopathological and histological features (11). As the presence of GISTs have been observed in numerous organs, including the urinary bladder (21), prostate (22), uterus (23), gall bladder (24) and myocardium (25), it can be assumed that EGISTs originate from common precursor cells that are able to differentiate into ICC-derived neoplasms outside of the gastrointestinal tract during development (26). An alternative explanation is that this type of tumor originates from the pluripotent mesenchymal stem cells located outside the gastrointestinal tract (10).…”
Section: Discussionmentioning
confidence: 99%
“…A literature review of the metastatic potential of GISTs identified one case of a “lump at the base of the penis” thought to be a metastatic lesion arising from a primary rectal tumor [8]. Although there have been no reported cases of metastatic GIST to the corpora of the penis, cases of GIST metastases to the prostate from primary rectal tumors are documented [9], [10], [11]. In this report, we describe the first documented case of metastatic GIST to the penis.…”
Section: Introductionmentioning
confidence: 99%